Financial contagion: Spillovers through banking centers - Caroline Van Rijckeghem; Beatrice Weder (Goethe University Frankfurt, Center for Financial Studies (CFS), 1999)
This paper presents evidence that spillovers through shifts in bank lending can help explain the pattern of contagion. To test the role of bank lending in transmitting currency crises we examine a panel of data on capital flows to 30 emerging markets disaggregated by 11 banking centers. In addition we study a cross-section of emerging markets for which we construct a number of measures of competition for bank funds. For the Mexican and Asian crises, we find that the degree to which countries compete for funds from common bank lenders is a fairly robust predictor of both disaggregated bank flows and the incidence of a currency crisis. In the Russian crisis, the common bank lender helps to predict the incidence of contagion but there is also evidence of a generalized outflow from all emerging markets. We test extensively for robustness to sample, specification and definition of the common bank lender effect. Overall our findings suggest that spillovers through banking centers may be more important in explaining contagion than similarities in macro-economic fundamentals and even than trade linkages.
urn:nbn:de:hebis:30-9664
Keywords: F30; F32; F34; 330; Contagion; Currency Crisis; Financial Spillovers